The effects of planting media and leaf fertilizers on the growth of jamrud orchid (Dendrobium macrophyllum A. Rich.) - I GEDE TIRTA (Society for Indonesian Biodiversity, 2006)
Jamrud orchid (Dendrobium macrophyllum A. Rich.) have attractive flowers which make the orchid become one of high economic ornamental plants. The orchid is one of endangered species. Its growth is slow, however appropriate planting media and leaf fertilizers can improve the growth of the orchid. The experiment was conducted from February to June 2003, at â€œEka Karyaâ€ Bali Botanic Garden. The design used in the experiment was completely randomized block with two treatments and four replicates. The first factor were six kinds of planting medias (roots of C. contaminans, roots of Asplenium nidus, charcoal, roots of C. contaminans+roots of A. nidus, roots of C. contaminans+charcoal and roots of A. nidus+charcoal). The second factor were four kinds of fertilizers (plant catalyst, super bionik, inabio and subur inti persada) and one treatment without fertilizer. The results of experiment showed that the interaction between planting medias and leaf fertilizers significantly affected increment of plant height at 12, 14, 16 and 18 weeks after planting, of leaf number at 14, 16 and 18 weeks after planting, of root length, of plant fresh weight and oven dry weight. Treatment of C. contaminans roots and of A. nidus roots combined with inabio fertilizer produced the highest vegetative growth. This treatment increased the total oven dry weight of plant (54.81%), increased the weight of plant (67.48%), of root length (41.63%), of total leaf number (70.73%), of plant height (59.01%) and bud number (72.22%) compared with treatment without fertilizer in the same media. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: planting media, leaf fertilizers, growth, Dendrobium macrophyllum A.Rich.